2001
DOI: 10.1161/01.cir.103.16.2084
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Arterial Responses to Treadmill Exercise Among Healthy Subjects and Atherosclerotic Patients

Abstract: Half of our CAD patients manifested diminution in PWA that was consistent with peripheral arterial vasoconstriction during the early phases of treadmill exercise. Such paradoxical vasoconstrictive responses were not observed in normal subjects and, therefore, they may represent generalized vascular pathology secondary to atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 15 publications
1
33
0
1
Order By: Relevance
“…[16][17][18][19][20][21][22][23][24][25][26][27][28] A com pen sa tory in cre a se in the com mon ca ro tid ar tery di a me ter is se en only in the yo ung con trol gro ups but not in the el derly hyper ten sives. [29][30][31] The re fo re, in cre a sing the blo od pres su re for com pen sa ti on is the ma in physi o lo gi cal way where as dec re a sing the vis co sity to in cre a se the Q (flow ra te) with he mo di lu ti on is a no nin va si ve way to res cu e the tis su e from isc he mi a for the at he rosc lero tic re gi on. 26,27,30,32 The aim of this study is to in ves ti ga te the re lati ons hips among tem pe ra tu re stress, blo od and plas ma vis co sity, blo od flow ra te, he art ra te, blo od pres su re, and pul se pres su re by using a flow chart of se mi clo sed system analy sis to eva lu a te the results.…”
Section: Fac Tors Af Fec Ting Blo Od Vis Co Sity and He Mody Na Micsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28] A com pen sa tory in cre a se in the com mon ca ro tid ar tery di a me ter is se en only in the yo ung con trol gro ups but not in the el derly hyper ten sives. [29][30][31] The re fo re, in cre a sing the blo od pres su re for com pen sa ti on is the ma in physi o lo gi cal way where as dec re a sing the vis co sity to in cre a se the Q (flow ra te) with he mo di lu ti on is a no nin va si ve way to res cu e the tis su e from isc he mi a for the at he rosc lero tic re gi on. 26,27,30,32 The aim of this study is to in ves ti ga te the re lati ons hips among tem pe ra tu re stress, blo od and plas ma vis co sity, blo od flow ra te, he art ra te, blo od pres su re, and pul se pres su re by using a flow chart of se mi clo sed system analy sis to eva lu a te the results.…”
Section: Fac Tors Af Fec Ting Blo Od Vis Co Sity and He Mody Na Micsmentioning
confidence: 99%
“…Rozanski et al 39 compared the peripheral blood flow response in 57 coronary patients and 50 apparently healthy individuals, submitted to physical exercise on an ergometric treadmill. The results showed that, among the healthy individuals, 76% showed vasodilation throughout the exercise, whereas 35% of the individuals with CAD showed progressive vasoconstriction.…”
Section: Chronic Failurementioning
confidence: 99%
“…RH-PAT has been extensively correlated to early and clinically relevant CAD. [84][85][86][87][88][89] For instance, RH-PAT results were significantly impaired in patients with exercise-induced myocardial ischemia. 87 More importantly, it is similar to FMD in representing a true physiological reflection of peripheral endothelial function, [90][91][92] and is particularly useful in conditions such as diabetes [93][94][95] or the metabolic syndrome 96,97 that impair endothelial function.…”
Section: Physiological Measurementsmentioning
confidence: 99%